A comparative phylogenetic analysis of medicinal plant Tribulus terrestris in Northwest India revealed by RAPD and ISSR markers - ASHWANI KUMAR; NEELAM VERMA (Society for Indonesian Biodiversity, 2012)
Kumar A, Verma N. 2012. A comparative phylogenetic analysis of medicinal plant Tribulus terrestris in Northwest India revealed by RAPD and ISSR markers. Biodiversitas 13: 107-113. Several DNA marker systems and associated techniques are available today for fingerprinting of plant varieties. A total of 5 RAPD and 8 ISSR primers were used. Amplification of genomic DNA of the 6 genotypes, using RAPD analysis, yielded 164 fragments that could be scored, of which 47 were polymorphic, with an average of 9.4 polymorphic fragments per primer. Number of amplified fragments with random primers ranged from 6 (AKR-1) to 10 (AKR-4) and varied in size from 200 bp to 2,500 bp. Percentage polymorphism ranged from 16% (AKR-4) to a maximum of 41% (AKR-4), with an average of 29.6%. The 8 ISSR primers used in the study produced 327 bands across 6 genotypes, of which 114 were polymorphic. The number of amplified bands varied from 7 (ISSR 7) to 12 (ISSR 1&3), with a size range of 250-2,800 bp. The average numbers of bands per primer and polymorphic bands per primer were 40.87 and 14.25, respectively. Percentage polymorphism ranged from 24% (ISSR 4) to 53.84% (ISSR 2), with an average percentage polymorphism of 35.59% across all the genotypes. The 3′-anchored primers based on poly (AC) and poly (AT) motifs produced high average polymorphisms of 53.84% and 40.81%, respectively. ISSR markers were more efficient than the RAPD assay, as they detected 35.59% polymorphic DNA markers in Tribulus terrestris as compared to 29.6% for RAPD markers. Clustering of genotypes within groups was not similar when RAPD and ISSR derived dendrogram were compared, whereas the pattern of clustering of the genotypes remained more or less the same in ISSR and combined data of RAPD and ISSR.